2017
DOI: 10.1113/ep086343
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in neuromuscular activation contribute to the knee extensor angle–torque relationship?

Abstract: What is the central question of the study? Do changes in neuromuscular activation contribute to the knee extensor angle-torque relationship? What is the main finding and its importance? Both agonist (quadriceps) and antagonist coactivation (hamstrings) differed with knee joint angle during maximal isometric knee extensions and thus both are likely to contribute to the angle-torque relationship. Specifically, two independent measurement techniques showed quadriceps activation to be lower at more extended positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 44 publications
8
38
0
Order By: Relevance
“…Thus, the adaptations of the training intervention at the present study could have occurred at supraspinal level at the trained angle and reflected as well in the other knee-joint angles. Additionally, hamstrings coactivation changes across knee-joint angles (Kubo et al 2004;Lanza et al 2017) and may have altered after the training intervention and reflected in our results. Moreover, mechanically, the cross-brigde binding is not optimall at more extended or flexed positions (Rassier et al 1999), which may also influence the adpations after training with higher responses where the binding is optimal.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, the adaptations of the training intervention at the present study could have occurred at supraspinal level at the trained angle and reflected as well in the other knee-joint angles. Additionally, hamstrings coactivation changes across knee-joint angles (Kubo et al 2004;Lanza et al 2017) and may have altered after the training intervention and reflected in our results. Moreover, mechanically, the cross-brigde binding is not optimall at more extended or flexed positions (Rassier et al 1999), which may also influence the adpations after training with higher responses where the binding is optimal.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, whether increases in agonist neuromuscular activation underpin joint angle specific strength increases after short-term SCT remains unclear. These contrasting findings may be due to a lack of contemporary sEMG methods such as joint angle specific M-wave normalization (Lanza et al 2017), duplicate sensors on each superficial constituent muscle (Balshaw et al 2017), and duplicate measurement sessions at each timepoint (i.e. pre and post training) to enhance measurement reliability.…”
Section: Introductionmentioning
confidence: 99%
“…The internal or external rotation of the humerus generates an increment in moment arm for posterior and anterior deltoid, respectively, thus increasing their activity [ 5 ]. Additionally, bi-articular muscles show greater sEMG RMS at long compared with short muscle length [ 27 , 28 ], possibly because of changes in moment arm and muscle architecture [ 29 ], modifications in both spinal and supraspinal mechanisms [ 30 ], or also changes in the characteristics of motoneurons pool when a muscle is lengthened [ 28 ]. Interestingly, although a computational study found that the humerus rotation could have led to negligible differences, here, the present competitive bodybuilders might have been able to increase the muscle activation for each exercise [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of the performance of a particular muscle group, it is fundamental, especially in the measurement of isometric strength, to standardize the joint angle on which this group acts, as well as that of the joints on which the agonist groups in that exercise are operating [36][37][38]. In general it is considered that the angle of knee flexion which produces the greatest isometric torque is between 80 and 90 • [36,39]; however, the angle of the patient's hip in the evaluation position also modifies the result of the force expressed. Therefore, the standardization of angles is necessary to be able to establish valid comparisons of results obtained in evaluations sequenced over time and for comparison with data from other studies.…”
Section: Discussionmentioning
confidence: 99%